PENGARUH KEBIASAAN BELAJAR DAN LINGKUNGAN FISIK TERHADAP HASIL BELAJAR - wardani, intan kusuma (Jurnal Informasi dan Komunikasi Administrasi Perkantoran, 2015)
ABSTRACTIntan Kusuma Wardani. THE EFFECT OF THE LEARNING HABIT AND  THE PHYSICAL ENVIRONMENT ON THE LEARNING RESULT IN DOCUMENT MULTIPLICATION HANDLING SUBJECT MATTER OF THE STUDENTS IN GRADE XI OF THE OFFICE ADMINISTRATION PROGRAM OF VOCATIONAL HIGH SCHOOL WIKARYA OF KARANGANYAR IN ACADEMIC YEAR 2012/2013. Skripsi: The Faculty of Teacher Training and Education, Sebelas Maret University Surakarta, July 2013.The objectives of this research are to investigate: (1) whether or not there is a significant effect of the learning habit on the learning result in Document Multiplication Handling subject matter of the students in Grade XI of the Office Administration Program of Vocational High School Wikarya of Karanganyar in Academic Year 2012/2013; (2) whether or not there is a significant effect of the physical environment on the learning result in Document Multiplication Handling subject matter of the students in Grade XI of the Office Administration Program of Vocational High School Wikarya of Karanganyar in Academic Year 2012/2013; and (3) whether or not there is a simultaneously significant effect of the learning habit and the physical environment on the learning result in Document Multiplication Handling subject matter of the students in Grade XI of the Office Administration Program of Vocational High School Wikarya of Karanganyar in Academic Year 2012/2013.This research used the descriptive quantitative research method. The population of the research was all of the students in Grade XI of the Office Administration Program of Vocational High School Wikarya of Karanganyar in Academic Year 2012/2013 as many as 91students. The samples of the research consisted of 51 students and were taken by using the proportionate random sampling technique. The data of the research were gathered through questionnaire and documentation. They were then analyzed by using the multiple linear regression technique of analysis.The results of the research are as follows: (1) there is a significant effect of the learning habit on the learning result in Document Multiplication Handling subject matter of the students in Grade XI of the Office Administration Program of Vocational High School Wikarya of Karanganyar in Academic Year 2012/2013 as indicated by the value of rcount = 0.506 > that of rtable= 0.276 at the significance level of 5% ; (2) there is a significant effect of the physical environment on the learning result in Document Multiplication Handling subject matter of the students in Grade XI of the Office Administration Program of Vocational High School Wikarya of Karanganyar in Academic Year 2012/2013 as shown by the value of rcount = 0.484 > that of rtable= 0.276 at the significance level of 5%; and (3) there is a simultaneously significant effect of the learning habit and the physical environment on the learning result in Document Multiplication Handling subject matter of the students in Grade XI of the Office Administration Program of Vocational High School Wikarya of Karanganyar in Academic Year 2012/2013 pointed out by the value of Fcount = 15.742 > that of rtable= 3.191 at the significance level of 5%.The multiple linear regression equation is ? = 26.769 + 0.547 X1 + 0.424 X2. The simultaneous contribution of the independent variables on the dependent variable (R2) is 39.6%. The relative contribution of the learning habit to the learning result is 52.85%, and that of the physical environment to the learning result is 47.15%. In addition, the effective contribution of the learning habit to the learning result is 20.93%, and that of the physical environment to the learning result is 18.68%.Keywords: Learning habit, physical environment, and learning result.